Genetic programming in the twenty-first century - De Lorenzo, Andrea (2022)
De Lorenzo, A., Bartoli, A., Castelli, M., Medvet, E., & Xue, B. (2020). Genetic programming in the twenty-first century: a bibliometric and content-based analysis from both sides of the fence. Genetic Programming And Evolvable Machines, 21(1-2), 181–204. [Adavanced online publication on 27 July 2019]. doi: https://doi.org/10.1007/s10710-019-09363-3